Three-dimensional array of microbubbles sonoporation of cells in microfluidics - Huang, Guangyong; Lin, Lin; Liu, Quanhui; Wu, Shixiong; Chen, Jiapeng; Zhu, Rongxing; You, Hui; Sun, Cuimin (Frontiers in Bioengineering and Biotechnology, 2024)
Sonoporation is a popular membrane disruption technique widely applicable in various fields, including cell therapy, drug delivery, and biomanufacturing. In recent years, there has been significant progress in achieving controlled, high-viability, and high-efficiency cell sonoporation in microfluidics. If the microchannels are too small, especially when scaled down to the cellular level, it still remains a challenge to overcome microchannel clogging, and low throughput. Here, we presented a microfluidic device capable of modulating membrane permeability through oscillating three-dimensional array of microbubbles. Simulations were performed to analyze the effective range of action of the oscillating microbubbles to obtain the optimal microchannel size. Utilizing a high-precision light curing 3D printer to fabricate uniformly sized microstructures in a one-step on both the side walls and the top surface for the generation of microbubbles. These microbubbles oscillated with nearly identical amplitudes and frequencies, ensuring efficient and stable sonoporation within the system. Cells were captured and trapped on the bubble surface by the acoustic streaming and secondary acoustic radiation forces induced by the oscillating microbubbles. At a driving voltage of 30 Vpp, the sonoporation efficiency of cells reached 93.9 ± 2.4%.